(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2017)
There are different types of public policies they are distributive, redistributive, regulatory, and the constituent public policy. The regulatory policies are aimed to regulate someone or some organizations from doing unlawful activities that are pre-determined by some act or legislations. The Real Estate (Regulation and Development) Act 2016 is a regulatory type of public policy that aimed at the regulation of some unsolicited activities that existed in the sale, construction, and development of real estate business. Being a developing and second-most populous country in the world, India requires building millions of houses for the poor, middle class, and the rich. It was a decades-long demand from different stakeholders to create legislation to control the illegal trends that existed in the real estate sector. The RERA, thus created, now act as a legal body that could control every type of bad trends from the real estate sector of India.As a regulatory policy, this law is important in its usefulness because the land for human existence is a close part of human life everywhere, especially to those who don’t have even a piece of land to dwell or those who need business space to do business and to the industrialists to start industries. This study gives thrust to the importance of the Real Estate (Regulation and Development) Act as a policy that could initiate changes in the behavioural pattern of those who are into this business. The popular outlook towards the regulatory type of public policies is sometimes different. Some believe that the regulations of any kind are against the principles of liberal democracies and some others believe that the regulations are necessary to control the corporates and greedy businessmen from exploiting the general public. Insofar as the Real Estate (Regulation and Development) Act 2016 is concerned, it is a real saviour of the millions of people who are aspiring to acquire a house as their own. For the creation of a just society, where the resources are justifiably distributed, we need to implement some serious policies which can control men form snatching the space that is common to all.